2021
DOI: 10.1097/mcc.0000000000000890
|View full text |Cite
|
Sign up to set email alerts
|

Blood purification in sepsis and systemic inflammation

Abstract: Purpose of reviewSepsis and septic shock are life-threatening diseases with high mortality. Although efforts have made to improve the survivals, the outcomes are still frustrating. Blood purification was thought to be a promising adjunctive therapy to regulate the excessive cytokine storm or to reduce the endotoxin activity caused by sepsis. Critically ill COVID-19 characterized with the similar disease to sepsis may also benefit from blood purification. Recent findingsThe recent studies mainly focused on hema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Several studies have demonstrated that the traditional continuous renal replacement therapy (CRRT) even in high doses, seem not to be able to remove efficiently inflammatory mediators produced in sepsis and to improve patient outcome [15] . The main reason could be the fact that traditional blood purification technologies are based on mechanisms of convention and diffusion and thus the removal of high molecular substances, such as cytokines, becomes non effective [16] . Even though, traditionally EBP methods have been recommended as adjuvant therapy for a serious overdose from toxins such as salicylates, lithium, ethylene glycol and methanol [17] , they were also used for treatment of severe disorders refractory to conventional therapies, such as fulminant liver failure, collagen diseases, and transplant rejection [18] .…”
Section: Apheresis Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that the traditional continuous renal replacement therapy (CRRT) even in high doses, seem not to be able to remove efficiently inflammatory mediators produced in sepsis and to improve patient outcome [15] . The main reason could be the fact that traditional blood purification technologies are based on mechanisms of convention and diffusion and thus the removal of high molecular substances, such as cytokines, becomes non effective [16] . Even though, traditionally EBP methods have been recommended as adjuvant therapy for a serious overdose from toxins such as salicylates, lithium, ethylene glycol and methanol [17] , they were also used for treatment of severe disorders refractory to conventional therapies, such as fulminant liver failure, collagen diseases, and transplant rejection [18] .…”
Section: Apheresis Techniquesmentioning
confidence: 99%
“…Over the last years, more sophisticated devices have been developed focused on the optimization of adsorption materials and anticoagulation techniques, in order to improve the removal of endotoxins and inflammatory mediators, such as cytokines/chemokines and coagulation factors [16] . Although bacterial sepsis is not a common feature of Covid- 19 infection, critically ill patients may also benefit from extracorporeal blood purification (EBP) therapies due to severe cytokine storm syndrome (CSS).…”
Section: Apheresis Techniquesmentioning
confidence: 99%
“…Studies in children with coronavirus disease 2019 suggest that anti-immune and anti-inflammatory therapies are beneficial for the targeted patients [7,8] . Blood purification with adsorption was also thought to be a potential adjunctive therapy for sepsis and systematic inflammation to regulate the excessive cytokine storm or reduce endotoxin activity [9] …”
mentioning
confidence: 99%
“…[ 7 , 8 ] Blood purification with adsorption was also thought to be a potential adjunctive therapy for sepsis and systematic inflammation to regulate the excessive cytokine storm or reduce endotoxin activity. [ 9 ]…”
mentioning
confidence: 99%
“…Recent advances in the development of new absorptive materials and hemoperfusion devices have motivated clinical studies in patients with sepsis, showing a significant decrease in circulating cytokine and endotoxin concentrations with favorable hemodynamic effects [ 27 ]. However, evidence from the clinical application of hemoperfusion is limited and controversial [ 28 ]. Large randomized controlled trials are needed to investigate the therapeutic role of blood purification modalities in sepsis.…”
mentioning
confidence: 99%